Evaluation of the Effectiveness of Standard Precaution Training on Disposition of Occupational Blood Exposure Among Healthcare Trainees: A Pre-Post Intervention Study - Zhang X; Li H; Li N; Li Y; Kong L; Zhang M; Wang P; Ma Y; Ni L; Liu L; Meng X (Advances in Medical Education and Practice)
Xing Zhang,1 Hongwei Li,2 Ning Li,1 Yusen Li,1 Li Kong,1 Min Zhang,1 Peng Wang,1 Yonghui Ma,1 Leiping Ni,2 Lili Liu,1 Xiujuan Meng1 1Healthcare-Associated Infection Control Department, Affiliated Hospital of Jining Medical University, Jining, Shandong, People’s Republic of China; 2Medical Education Center, Affiliated Hospital of Jining Medical University, Jining, Shandong, People’s Republic of ChinaCorrespondence: Xiujuan Meng, Healthcare-associated infection control department, Affiliated Hospital of Jining Medical University, Jining, Shandong, People’s Republic of China, Tel +86 537 2903180, Fax +86 537 2213030, Email mxj0324@163.comIntroduction: Blood-borne occupational exposure (OBE) is one of the major public health problem for healthcare workers globally. Effective education and training on post-exposure management and standard precautions for healthcare trainees, are important measures for reducing OBE and infection rates. The aim of this study was to evaluate the effectiveness of standard precaution training on OBE disposition for healthcare trainees, comparing the differences of “theoretical teaching” and “situational simulation” training methods.Methods: A pre-post intervention study was conducted among 1347 healthcare trainees at a university teaching hospital located in Jining, Shandong Province from July 2023 to September 2023. Healthcare trainees who were undergoing training at the hospital from July 2020 to July 2023 were selected as the research subjects. They voluntarily participated in theoretical teaching group or situational simulation group. The two groups taught the same knowledge using different methods. Both groups were tested the same content before and after the training.Results: The accuracy rates before and after training in different groups were 71.71% and 78.08%, respectively (P< 0.001). The accuracy rate after training in the scenario simulation group (79.08%) was higher than that in the theoretical teaching group (76.60%), with a statistically significant difference (P< 0.05). The accuracy rate for trainees who experienced OBE was 69.87% before training and 77.11% after training. For trainees who had not experienced OBE, the accuracy rates were 71.38% before training and 77.25% after training. The accuracy rates were higher after training compared to before training, with statistically significant differences (P< 0.001).Conclusion: Scenario simulation training exhibits significant advantages in improving accuracy due to its strong practicality, high level of participation, and timely feedback. The self-protection awareness, knowledge on OBE management, and standard precaution among healthcare trainees were enhanced through the training, and operational content can achieve better results through scenario simulation training.Keywords: healthcare trainees, occupational blood exposure, standard precaution, theoretical teaching, situational simulation